STUDI KASUS KEMAMPUAN LITERASI DIGITAL ABAD 21 GURU SD DI BANJARMASIN - Jamilah, Jamilah; Sadiqin, Ikhwan Khairu; Zulkarnain, Akhmad (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
Research has been conducted to describe the digital literacy of elementary school teachers in Banjarmasin. This research serves to provide an overview of elementary school teachers' literacy and the obstacles in Banjarmasin. The research is quantitative descriptive. The sample selection technique was purposive sampling. The subjects were 109 elementary school teachers in Banjar District. The results of this research are that teachers at elementary schools in Banjarmasin tend to have digital literacy skills in the good category. The average score reached 76.33%. The aspect of ability that teachers master most is information and data literacy which is in the good category at 83.64%. The security aspect is in the good category at 76.26%. The communication and collaboration aspects are in the good category at 70.87%. The problem solving aspect is in the good category at 80.73%. The digital content creation aspect is in the good category at 71.99%. Digital literacy is good mastered because it is supported by the independent learning program and community of peer teachers. Teachers lack mastery of aspects of digital content creation, seen from the lowest competency, this is because teachers prefer to use ready-made teaching media and lack the desire to create digital content.